2019
DOI: 10.1111/apha.13317
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐9‐positive neutrophils are essential for establishing profibrotic microenvironment in the obstructed kidney of UUO mice

Abstract: Aim: Matrix metalloproteinase-9 (MMP9) plays a profibrotic role in renal fibrosis. Neutrophils produce MMP9 in many pathologic models. However, the effect of neutrophil on the progression of renal fibrosis and the relationship of MMP9 to the infiltration of neutrophils into the kidney remain unknown. Methods: The surgery of unilateral ureter obstruction (UUO) was performed in male C57BL/6 mice. Kidneys were collected for analyses on days 0, 1, 3, 5 or 7 following surgery. The inflammatory cells were analysed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
(77 reference statements)
3
30
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are known to play a central role in fibrosis through their ability break down ECM constituents. Recent studies have also suggested a role for MMP upregulation in sustained inflammation through the immune cells chemoattraction and proliferation [ 54 , 55 ], particularly in older individuals [ 56 ], suggesting a role of MMP’s in the highly interdependent age and skin score correlations revealed through our Bayesian network projections ( Fig 2 ). Along with several other MMPs and their inhibitors, levels of MMP-1 show close association with SSc, and we found that gene expression differed between dSSc and lSSc patient profiles ( Fig 6 ).…”
Section: Discussionsupporting
confidence: 52%
“…Matrix metalloproteinases (MMPs) are known to play a central role in fibrosis through their ability break down ECM constituents. Recent studies have also suggested a role for MMP upregulation in sustained inflammation through the immune cells chemoattraction and proliferation [ 54 , 55 ], particularly in older individuals [ 56 ], suggesting a role of MMP’s in the highly interdependent age and skin score correlations revealed through our Bayesian network projections ( Fig 2 ). Along with several other MMPs and their inhibitors, levels of MMP-1 show close association with SSc, and we found that gene expression differed between dSSc and lSSc patient profiles ( Fig 6 ).…”
Section: Discussionsupporting
confidence: 52%
“…To test whether or not the neutrophils play a role in the development of kidney fibrosis in this model the authors used neutrophil depletion by means of Ly6G antibody injection. Interestingly, interstitial collagen deposition was lower in the neutrophil‐depleted mice as compared to the isotype‐antibody treated obstructed mice 1 . The authors found by immunohistochemical staining that neutrophils are an important source for MMP9 in the obstructed kidney.…”
mentioning
confidence: 91%
“…Kidney research has been one major focus of publications of recent articles published in Acta physiologica . A number of articles deal with the elucidation of kidney disease models 1‐12 and the role of oxygen regulation in the kidney 13‐16 . This contribution focusses on articles that deal with kidney disease models and in the second part on articles that are related to the topic hypoxia and oxygen regulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations